Design and Develop a Web-Based Extracurricular Activity Reporting Information System at SMK YAPERMAS - Alfarizi, Alfarizi; Sudarsono, Bernadus Gunawan; Sharyanto, Sharyanto (Journal of Engineering, Technology and Computing (JETCom), 2024)
Extracurricular activities are activities held outside class hours listed in the student activity program structure. Foundation Vocational School Jakarta Community College (SMK YAPERMAS) is one of the educational institutions under the care of the Community College Foundation operating in the field of education. Currently managing extracurricular data and registration of students taking part in extracurricular activities is still being carried out manually or not yet systematized, namely recording and registering students who take part in extracurricular activities still use paper forms where there is no complete information regarding extracurricular activities. Not yet available means of managing extracurricular activities at school because they are lacking in depth utilize information technology. The aim of this research is design build a website information system to support activity management extracurricular at YAPERMAS Vocational School by utilizing the application database based. Laravel was chosen to build this application It is hoped that this will make extracurricular registration and management easier extracurricular so that it is faster and more accurate.